2012
DOI: 10.1149/2.052208jes
|View full text |Cite
|
Sign up to set email alerts
|

A Functionalized Co2P Negative Electrode for Batteries Demanding High Li-Potential Reaction

Abstract: Co-P alloy films were electrodeposited on a titanium electrode. The controlled addition of phosphorous acid or sodium hypophosphite to a Co 2+ -containing solution leads to the formation of amorphous or crystalline CoP phases. Particularly, the orthorhombic Co 2 P phase is obtained at 80 • C with a current density of 37.5 mA cm −2 during 10 and 20 min as determined by XRD and XPS analysis. The morphology of Co 2 P can be controlled from leopard-like spots to hexagonal symmetric particles as confirmed by SEM. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The three extra peaks are thought also from the bonding between GeP 5 and carbon, since similar extra XPS peaks have been identified for the P-C bonds by Cui et al in the composite of black P and carbon. As shown in Figure 7a , the GeP 5 electrode after discharging to 0.005 V clearly exhibits the XRD peaks of Li 22 Ge 5 (Li 4.4 Ge) and Li 3 P phases, [27][28] which evidences the large capacity of GeP 5 comes from the contribution of both Ge and P. According to this, the electrode reaction of GeP 5 can be described by the following equations: 15 34,42 CV measurements on GeP 5 /C in comparison of Ge/C and P/C composites further comfirm the above Li storage mechanism. On the one hand, the carbon network provides directional electron-transport paths and tight electronic contact between the active nanoparticles, so that electrons can be quickly transferred from the active sites to the electrode current collector along the carbon superhighway.…”
Section: Resultsmentioning
confidence: 97%
“…The three extra peaks are thought also from the bonding between GeP 5 and carbon, since similar extra XPS peaks have been identified for the P-C bonds by Cui et al in the composite of black P and carbon. As shown in Figure 7a , the GeP 5 electrode after discharging to 0.005 V clearly exhibits the XRD peaks of Li 22 Ge 5 (Li 4.4 Ge) and Li 3 P phases, [27][28] which evidences the large capacity of GeP 5 comes from the contribution of both Ge and P. According to this, the electrode reaction of GeP 5 can be described by the following equations: 15 34,42 CV measurements on GeP 5 /C in comparison of Ge/C and P/C composites further comfirm the above Li storage mechanism. On the one hand, the carbon network provides directional electron-transport paths and tight electronic contact between the active nanoparticles, so that electrons can be quickly transferred from the active sites to the electrode current collector along the carbon superhighway.…”
Section: Resultsmentioning
confidence: 97%
“…13 Cobalt phosphides, which have been extensively studied in many fields (e.g., as electro-catalysts in water splitting, as anode materials in lithium-ion batteries, and as catalysts in hydrodesulfurization reactions), exhibit metalloid properties and superior electronic conductivity. [14][15][16][17][18][19][20][21] Since both cobalt phosphates and nickel phosphides have delivered high specific capacitance for supercapacitors in previous demonstrations, 11,22,23 cobalt phosphides can be reasonably believed to produce rich redox reactions in alkaline solution. Moreover, considering the relationship between cobalt oxides and nickel oxides, 24,25 cobalt phosphides should have a higher theoretical capacity than nickel phosphides.…”
Section: Introductionmentioning
confidence: 99%
“…As an important class of magnetic metal phosphides, cobalt phosphides have been investigated for their special magnetic [24,25] and catalytic properties [26,27]. Recently, studies on the electrochemical performance of cobalt phosphide nanomaterials have indicated that they can be used as anode materials for potential applications in lithium ion batteries [28,29]. In comparison, reports on the electrocatalytic HER performance of nanoscale cobalt phosphides are very rare.…”
Section: Introductionmentioning
confidence: 99%